Safety profiles of doxycycline, minocycline, and tigecycline in pediatric patients: a real-world pharmacovigilance analysis based on the FAERS database - Qiao, Yanli; Chen, Yechao; Wang, Qiaoyun; Liu, Jingrui; Guo, Xiaohui; Gu, Qiaoling; Ding, Peng; Zhang, Haixia; Mei, Hongliang (Frontiers in Pharmacology, 2024)
Introduction: Recently, the rise of antibiotic resistance has prompted a reconsideration of tetracyclines. However, existing studies are inadequate in assessing the pediatric safety of this class of antibiotics. To address the gap, our study aims to comprehensively assess the safety of tetracyclines in children.Method: Adverse event (AE) reports from January 2005 to September 2023 were obtained from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database, and reporting odds ratio (ROR) was performed to identify potential risk signals in children under 18 years old who were administered any of the three tetracyclines: doxycycline, minocycline, and tigecycline.Results: A total of 1903 AE cases were included in our study: 782 for doxycycline, 981 for minocycline, and 140 for tigecycline. Doxycycline and tigecycline were predominantly associated with "general disorders and administration site conditions" and "gastrointestinal disorders," while minocycline was more frequently linked to "skin and subcutaneous tissue disorders" and "gastrointestinal disorders." Psychiatric risks predominantly included depression, suicidal ideation, and suicide attempt. In the category of skin and subcutaneous tissues, 30.88% of the minocyclineinduced drug reaction with eosinophilia and systemic symptoms (DRESS) cases resulted in death, alongside a high occurrence of co-occurring AEs such as multiple organ dysfunction syndrome, Type 1 Diabetes Mellitus (T1DM), and autoimmune thyroiditis. As for the endocrine system, both doxycycline and minocycline were found to potentially increase the risk of thyroid dysfunction. For children under the age of 8, doxycycline was associated with tooth discoloration (N=7, ROR=20.11, 95% CI: 9.48-42.67), although it remained unclear whether the discoloration was permanent. Conclusions: Our findings indicated that for pediatric patients, the majority of results were in line with the prescribing information and previous studies, and minocycline tended to cause more frequent and severe AEs than doxycycline. However, it is noteworthy that exceptions were found for psychiatric disorders and thyroid dysfunction associated with doxycycline, which are not mentioned in its FDA prescribing information. Additionally, further safety studies on tigecycline are still needed for children. When prescribing tetracyclines to pediatric patients, a careful risk-benefit assessment is crucial.